Heat transfer enhancement and investigation on Stirling engine heater with biomass application - Punsa Tuntrakeun; Panya Kansuwan; Sutapat Kwankaomeng (My University, 2021)
This research presents a heat transfer enhancement technique on a Stirling engine heater equipped with a biomass fuel burner. ANSYS Fluent software was utilized in the computation of heat transfer, including heat flux and temperature distribution on the heater component of the engine. Effects of the increasing of the heating surface on heat transfer enhancement were investigated. Fin effectiveness resulting from the fin parameter variation of the heater, such as fin diameter and fin spacing, was evaluated for heat transfer under forced convection and heat conduction. This simulation results in the fin configuration most suitable for the fabrication of our Stirling engine heater.
Keywords: Fin; Advanced Thermodynamic Systems and Engines